Cefotaxime and amikacin combination in the treatment of Salmonella infection in premature infants - Oran, Olcay; Yurdakök, Murat; Tekinalp, Gülsevin; Kanra, Güler (The Turkish Journal of Pediatrics, 1988)
This study included twelve premature infants with Salmonella typhimurium infection in most of whom previous antibacterial therapy had failed. Cefotaxime and amikacin combination cured nine of the patients. One patient improved as a result of this therapy but had cholecystitis. The treatment proved to be unsuccessful in three patients, and they died.